Pre-Service Teahers’ Use of Mobile-Based Mindfulness Practices During Covid-19 Pandemic Era - Lingga A Suganda; Zuraida Zuraida; Ismail Petrus; Fiftinova Fiftinova (Jurnal Pendidikan Bahasa dan Sastra, 2022)
Mindfulness is the basic human ability to be fully present, aware of where they are and what they are doing, and not overly reactive or overwhelmed by what is going around them. The growing evidence of the use of mindfulness practice on promoting psychological wellbeing and self-regulation is in line with the increasing use of mobile applications in this digital era nowadays especially during the COVID-19 pandemic era. This study aims to find out the influence of two mobile-based mindfulness apps, Calm and Headspace, on the pre-service teachers of English as a Foreign Language (EFL) in Indonesia studying online during COVID-19 pandemic era. The 43 subjects were given 20-session-mindfulness intervention (guided and independent trainings) using the two mobile-based mindfulness apps. The data from the Five Facet Mindfulness Questionnaire (FFMQ), the classroom observations, and the written interviews were analysed quantitatively and qualitatively. The results from the t-test analysis on the FFMQ show that there was an improvement on the subjects’ mindfulness level after the intervention. Furthermore, the results of the observation and the interview show that the oral narrations of the contents in the apps were found useful as a means to provide positive learning environment before and during the learning practice. Moreover, the oral narrations of the contents in the apps were specifically found useful as a means to practice listening comprehension. Therefore, besides being served as a means to practice and improve the pre-service teachers’ mindfulness level, mobile-based mindfulness apps could also be used to enhance one’s English listening comprehension skills. The use of mobile-based mindfulness applications can be promising for pre-service teachers in Indonesia who need to have balance academic and social-emotional skills to support their role in teaching students in the future.